Experimental Investigations on the Effects of Dissolved Gases on the Freezing Dynamics of Ocean Worlds. Issue 8 (7th August 2020) - Berton, Mateo; Nathan, Erica; Karani, Hamid; Girona, Társilo; Huber, Christian; Williard, Paul G.; Head, James
Abstract: The surfaces of icy moons are covered by fractures, other tectonic features, and active or ancient remains of cryovolcanism. These observations suggest active or recent tectonics, but there is still much unknown about the specific conditions surrounding the formation of these features. One important process leading to the fracture of the ice shell is the freezing and consequent pressurization of its ocean, because water expands upon freezing. However, the influence of dissolved non‐condensable gases (herein referred to as volatiles) on the aforementioned dynamics remains poorly constrained. In this study, we present a new experimental investigation to explore the effect of dissolved volatiles in the internal pressure evolution of 10 cm diameter water spheres subjected to freezing temperatures between ~−60°C and ~−20°C. Our experiments reveal that spheres with a reduced initial amount of volatiles dissolved undergo an abrupt transition with dramatic increase of (a) the time between consecutive ice shell fractures and (b) the pressure required to break the shell. We show from a simple numerical model that this transition occurs when exsolution (i.e., nucleation and growth of bubbles) occurs and the fluid inside the shell becomes significantly more compressible. Exsolution is, in turn, triggered by the gradual thickening of the ice shell, which increases the concentration of dissolved volatiles and eventually leads to saturation. These results suggest that the content of volatiles of icy satellites plays a significant role in their geologic history and potential for habitability. Plain Language Summary: Icy moons have subsurface oceans which may be freezing. As water freezes, it expands. When a subsurface ocean on an icy moon freezes, this expansion of the ice shell increases the pressure in the ocean and can lead to the formation of water‐filled cracks in the icy surface of the moon. To understand how the amount of gas in the ocean water controls when the cracks form, we freeze small spheres of water with different amounts of air under controlled temperature. We find that at some point during the freezing and growth of the ice shell, there is a sharp change in how often cracks occur. This happens because dissolved gases remain in the liquid water during freezing and eventually there is enough gas in the water for bubbles to form. This is important because it tells us how the gas content in the oceans of icy moons might control some of the cracks we observe on the surface of icy moons. Key Points: The freezing of an ocean world is modeled experimentally by freezing spheres of water Increased dissolved volatiles in the water significantly influence the tectonic evolution of the body, leading to a lower frequency of fracture events and thinner ice shell at final failure These results have implications for the geologic history and habitability of icy moons. Specifically, oceans become more volatile‐rich over time, which in turn decreases the frequency at which the ice shell fractures